Using Stata for quantitative analysis - Longest, Kyle C. (Sage, 2020)
Using Stata for Quantitative Analysis is an applied, self-teaching resource that allows a reader with no experience with statistical software to sit down and work with data in a very short amount of time. Kyle C. Longest teaches the features and capabilities of stata from an intuitive perspective, furthering students' overall retention by using many screen shots from stata to guide students through the process. The self-teaching style of the text allows novice stata users the ability to complete a basic quantitative research project from start to finish."--Publisher's website